2022
DOI: 10.17239/jowr-2022.13.03.04
|View full text |Cite
|
Sign up to set email alerts
|

Writer/reader visibility in young learner writing: A study of the TRAWL corpus of lower secondary school texts

Abstract: A pervasive finding in learner corpus research is that advanced EFL learners tend to overuse interactional features of writer/reader visibility (WRV) in their written academic texts, including first-and second-person pronouns, I think, modal adverbs, modal auxiliaries, and questions. Very little research has been done on younger learners, however. The present study is a mixed-methods investigation of WRV features in argumentative and expository genres in the TRAWL longitudinal corpus of learner texts from Norw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Currently, this subset consists of all the English texts written by one class throughout lower secondary school (years 8-10). Hasund and Hasselgård (2022), who studied this set of texts, found that the six main genres/text types of argumentative, expository, descriptive, dialogic, reflective and narrative texts were all represented, with a predominance of narrative texts in the first year and argumentative and expository texts in the last year.…”
Section: Textsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, this subset consists of all the English texts written by one class throughout lower secondary school (years 8-10). Hasund and Hasselgård (2022), who studied this set of texts, found that the six main genres/text types of argumentative, expository, descriptive, dialogic, reflective and narrative texts were all represented, with a predominance of narrative texts in the first year and argumentative and expository texts in the last year.…”
Section: Textsmentioning
confidence: 99%
“…Since the corpus contains a large number of texts written as ordinary schoolwork, researchers must take care to select students and texts to suit their research questions and control important variables. For example, Hasund and Hasselgård (2022), who looked at features of writer/reader visibility, selected only argumentative and expository writing from the subset of texts annotated for genre (see Section 3). Dirdal (2022b), who investigated complexity development, selected only certain text types in order to ensure that the results were not skewed by the varying proportions of genres over the school years 6 .…”
Section: Use and Potentialmentioning
confidence: 99%
“…Both are written corpora with English L2 texts produced by Norwegian learners and have been used in a number of studies of Norwegian advanced learner English (See e.g. Hasselgård & Johansson, 2011;Paquot et al, 2013;Hasselgård, 2015;Larsson et al, 2020;Granger & Larsson, 2021;Ebeling & Hasselgård, 2021;Hasund & Hasselgård, 2022). ICLE-NO consists of 317 argumentative essays (about 214,000 words) collected between 1999 and 2002 (Johansson, 2008, p. 116;Granger et al, 2020, p. 33).…”
Section: The Norwegian Contextmentioning
confidence: 99%
“…The present study has not exploited the longitudinal nature of the TRAWL data, as the main aim was to explore the genre categories themselves rather than tracking how the distribution of genres develops as the pupils progress through secondary school. A longitudinal perspective is adopted in Hasund and Hasselgård (2022) and Hasselgård (2022), two studies which are both based on the genre subset, but more longitudinal studies are needed. Furthermore, as the TRAWL corpus includes teachers' written feedback on learner texts, another area of research could be to explore the extent to which teachers focus on genre in their feedback, as part of their L2 English writing instruction.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…However, it does have the consequence that the distinction between high and low-complexity writing becomes blurred (cf. Hasund & Hasselgård, 2022). This could have some negative effects, one of which being that pupils become less well prepared for academic, high-complexity writing at upper secondary and tertiary levels of education.…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%